Correction: Influence of permittivity and energetic disorder on the spatial charge carrier distribution and recombination in organic bulk-heterojunctions. Issue 21 (17th May 2019) - Albes, Tim; Gagliardi, Alessio
Abstract : Correction for 'Influence of permittivity and energetic disorder on the spatial charge carrier distribution and recombination in organic bulk-heterojunctions' by Tim Albes et al., Phys. Chem. Chem. Phys., 2017, 19, 20974–20983.